Task-based Activities in TEFL - Fachrurrazy, Fachrurrazy (TEFLIN Journal, 2015)
This article presents a discussion of task-based approach in Communicative Language Teaching. A task is a classroom activity involving learner’s interaction in which the main attention is on the meaning more than on the form of the target language. This approach may be applicable to TEFL in Indonesian context.